Introduction: Aeolian sediments and environments (IAS Meeting, Schladming, Austria, 2012) - Rodríguez Lopez, Juan Pedro (2013)
This special issue includes papers originally presented as part of the Scientific Session ‘‘Aeolian Sediments and Environments’’ during the 29th IAS Meeting of Sedimentology, September 10–13th, 2012 in Schladming, Austria. This scientific session was attended by an international community of geologists with interest in aeolian processes, environments and their complex depositional systems. Contributions dealing with multidisciplinary approaches to gaining an improved understanding of the controls operating on aeolian systems from both modern and ancient settings were received.